Effects of maximizing on choosing a product and using it over 1 month. (October 2022) - Polman, Evan; Maglio, Sam J.
Abstract: It is well documented that maximizers are less happy with their product-choices than are satisficers, but would this mean that maximizers use their products less? We conducted two studies and found that, contrary to scores of studies that demonstrate maximizers regret their decisions, maximizers consume their selected options with more gusto than satisficers. Our results thus contribute to research on maximizing and specifically the "maximization paradox"—the notion that maximizers make better choices than satisficers yet feel worse. Taking a post-choice perspective to maximizing, we examined the paradox after a choice is made. In addition, our research sheds new light on scholarship in consumer behavior. Rich with scientific insights that reveal how to promote, nudge, or alter a product-choice, research in consumer behavior has rarely tested what naturally follows: how much a chosen product is used or consumed. Over two 1-month periods, we examined how much maximizers consumed their selected options, which illuminates the realm of post-choice behavior—the degree that consumers use a product after acquiring it.